(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of patient safety knowledge among nurses and midwives at the National Hospital of Obstetrics and Gynecology in 2024. Subjects and methods: A cross-sectional descriptive study was conducted on 520 nurses and midwives working at the National Hospital of Obstetrics and Gynecology from August 2024 to May 2025. Results: The overall rate of adequate patient safety knowledge among nurses and midwives was 67.9%. The highest level of knowledge was observed in the criterion accurate patient identification (80.4%); followed by prevention of patient falls (76%), effective communication improvement (74%), safe surgical practice management (70.2%), and safe medication use (57.5%); the lowest score was recorded in infection risk management with only 48.5% of respondents demonstrating adequate knowledge. Conclusion: This study provides valuable practical evidence that serves as a basis for monitoring and evaluating patient safety knowledge among healthcare workers. It also highlights the need for targeted interventions to improve knowledge, with a particular emphasis on strengthening infection control practices.